A Research on Cloud Computing Challenges in Virtualization and Cloud Environment - Sardana, Vaibhav; Saxena, Nidhi (International Journal of Computer Sciences and Engineering, 2019)
Virtualization allows for multiple virtual machines or users to be logically segregated and access simultaneously the same physical machine from remote locations. It enables the cloud characteristics of resource pooling and multi-tenancy. Moreover it introduces the rapid elasticity feature and optimal management of resources. Virtualization supports the cloud in implementing its service and deployment models. Virtual machines can be created, copied and migrated which leads to security challenges. This paper elaborates on virtualization vulnerabilities and presents solutions existing in literature to the security threats.